Building a Systemic Integrity Model: Lessons from Australia’s Anti-Corruption and Integrity Reforms under the Open Government Partnership - Afandi, Syed Agung; Afandi, Muslim; Erdayani, Rizki (Global and Policy Journal of International Relations, 2026)
This study examines how Australia’s Open Government Partnership National Action Plan 2023–2025 operationalizes transparency, accountability, and integrity through a coherent governance framework. Moving beyond compliance-oriented transparency, Australia’s Open Government Partnership commitments integrate ethical norms, institutional coordination, and participatory accountability to construct a Systemic Integrity Governance Model. Using a theory-guided qualitative approach, this research analyzes policy documents, Open Government Partnership progress reports, and government integrity frameworks to identify the systemic linkages among openness, integrity, and anti-corruption mechanisms. The findings reveal that the five commitments—integrity strategy for the commonwealth public sector, beneficial ownership requirements, integrity and accountability in procurement and grants, public sector whistleblower protections, and transparent political donations and advertising—collectively form an integrated governance architecture. This model embeds integrity as both a moral and operational principle, aligning ethical conduct with institutional performance. The study contributes to the theory of open government by conceptualizing Systemic Integrity Governance as an evolutionary stage where transparency, integrity, and participation function as interdependent mechanisms for sustainable public trust and democratic resilience.